2020
DOI: 10.1111/iwj.13315
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis on the effect of Z‐plasty versus conventional simple excision for the treatment of sacrococcygeal pilonidal sinus: A retrospective randomised clinical study

Abstract: Sacrococcygeal pilonidal sinus is one of common diseases in general department. However, it is characterised, for surgeons, by high post‐surgical recurrence and high incidence of post‐surgical wound complications. Due to that fact, this retrospective randomised clinical study was designed to evaluate the surgical procedure effect of Z‐plasty (ZP), compared with convention simple excision (SE). A total of 67 patients from May 2015 to May 2019 in our department were studied into two groups randomly, the group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Although the complete recovery time was not measured, it was concluded that Z-plasty patients needed less time for total recovery than patients who underwent a simple excision. (32) B.N. Anandaravi et al compared two techniques in pilonidal sinus treatment: primary closure and laying open.…”
Section: 2-wound Healing Durationmentioning
confidence: 99%
“…Although the complete recovery time was not measured, it was concluded that Z-plasty patients needed less time for total recovery than patients who underwent a simple excision. (32) B.N. Anandaravi et al compared two techniques in pilonidal sinus treatment: primary closure and laying open.…”
Section: 2-wound Healing Durationmentioning
confidence: 99%
“…5 Negative pressure drainage techniques have been found to stimulate granulation tissue growth, reduce edema and wound contamination, and accelerate wound healing. 6 Currently, there are limited clinical studies on the effectiveness of sinus resection combined with vacuum-assisted closure in the treatment of sacrococcygeal pilonidal sinus. In this study, we investigated the application value of sinus resection combined with closed negative pressure drainage of the wound surface in 62 patients with sacrococcygeal pilonidal sinus.…”
Section: Introductionmentioning
confidence: 99%
“…Negative pressure drainage techniques have been found to stimulate granulation tissue growth, reduce edema and wound contamination, and accelerate wound healing 6 . Currently, there are limited clinical studies on the effectiveness of sinus resection combined with vacuum‐assisted closure in the treatment of sacrococcygeal pilonidal sinus.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent disease with its concomitant morbidity remains a concern, and no single therapeutic option has acquired general acceptability. [5–12]…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent disease with its concomitant morbidity remains a concern, and no single therapeutic option has acquired general acceptability. [5][6][7][8][9][10][11][12] In recent years, people are more and more inclined to minimally invasive surgery. Minero et al [13] introduced a more minimally invasive approach for sacrococcygeal pilonidal disease named Endoscopic Pilonidal Sinus Treatment in 2013 (EPSiT).…”
Section: Introductionmentioning
confidence: 99%